Standarisasi Simplisia Kering Daun Kelor (Moringa oleifera) Dari Tiga Daerah Berbeda - Bata, Maria H C; Wijaya, Sumi; Setiawan, Henry K (Jurnal Farmasi Sains dan Terapan, 2018)
Miracle tree (Moringa oleifera) is known for its many benefits, and has been used in traditional medicine. This study aims to determine macroscopic and microscopic characteristics of Miracle tree leaves and to determine specific and non specific parameter os standardization of Miracle tree dried powder. Miracle tree dried powder was obtained from three different locations (Batu, Bogor and Pacet). Determination of specific parameter of Miracle tree dried powder include macroscopic, microscopic, determination of soluble extract, chromatogram pattern determination by TLC, determination of infrared spectrum profile (IR), determination of UV spectrum profile and determination of quantitative secondary metabolite compounds. Non specific parameters including determination of total ash content, ash content water soluble, acid soluble ash content, drying shrinkage and pH. Determinations of quantitative secondary metabolite compounds were done using colorimetric method. Based on the results, Miracle tree dried powder contain alkaloid, flavonoids, polyphenols, saponins, tannins, steroids and triterpenoids. Ethyl acetate: n-hexan (7: 3 v / v) can be used as eluent on thin layer chromatography. Miracle tree dried powder gave wave number of 3277 – 3281, 2917 – 2918, 2849 – 2850, 1603 – 1607, 1408, 1235 – 1236, 1048 – 1051, 889, 534 – 536 and 452 - 455. Miracle tree dried powder gave standardization value of dried shrink rate 5.5% w/ w and total alkaloid content> 1.0% w/w.